Edukasi Penerapan Perilaku Hidup Sehat (PHBS) di Gampong Geundrieng - Rita Zahara; Ulvia Rahmi (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Health education plays a crucial role in improving community awareness and promoting healthy lifestyles, particularly in rural areas such as Gampong Geundrieng. This study aims to analyze the implementation and impact of healthy living education programs in enhancing community behavior related to Clean and Healthy Living Behavior (PHBS). The method used in this study is a descriptive qualitative approach, involving observation, interviews, and documentation of community activities related to health practices. The results indicate that health education initiatives in Gampong Geundrieng have contributed positively to increasing public knowledge about personal hygiene, environmental sanitation, and disease prevention. Activities such as counseling sessions, community discussions, and practical demonstrations have encouraged residents to adopt healthier habits, including regular handwashing, proper waste management, and maintaining clean living environments. However, several challenges remain, such as limited access to health facilities, lack of consistent community participation, and insufficient monitoring of behavioral changes. Furthermore, the role of local leaders and health workers is found to be essential in influencing and sustaining community engagement. Their involvement helps bridge the gap between health information and its practical application in daily life. Continuous education and community-based approaches are necessary to ensure long-term behavioral change and improved public health outcomes. In conclusion, healthy living education in Gampong Geundrieng has shown promising results in raising awareness and encouraging healthier practices among residents. Nevertheless, ongoing support, collaboration, and evaluation are needed to overcome existing barriers and to strengthen the effectiveness of health education programs in the community.